Hearing rehabilitation of adults with auditory processing disorder: a systematic review and meta-analysis of current evidence-based interventions - Crum, Rachel; Chowsilpa, Sanathorn; Kaski, Diego; Giunti, Paola; Bamiou, Doris-Eva; Koohi, Nehzat (Frontiers in Human Neuroscience, 2024)
For adults with auditory processing disorder (APD), listening and communicating can be difficult, potentially leading to social isolation, depression, employment difficulties and certainly reducing the quality of life. Despite existing practice guidelines suggesting treatments, the efficacy of these interventions remains uncertain due to a lack of comprehensive reviews.Objective: This systematic review and meta-analysis aim to establish current evidence on the effectiveness of interventions for APD in adults, addressing the urgent need for clarity in the field.Following the Preferred Reporting Items for Systematic reviews and Meta-Analyses (PRISMA) guidelines, we conducted a systematic search across MEDLINE (Ovid), Embase (Ovid), Web of Science and Scopus, focusing on intervention studies involving adults with APD. Studies that met the inclusion criteria were grouped according to intervention with a meta-analysis only conducted where intervention, study design and outcome measure were comparable.Out of 1618 screened records, 13 studies were included, covering auditory training (AT), lowgain hearing aids (LGHA), and personal remote microphone systems (PRMS). Our analysis revealed:AT: Mixed results with some improvements in speech intelligibility and listening ability, indicating potential benefits but highlighting the need for standardised protocols.LGHA: The included studies demonstrated significant improvements in monaural low redundancy speech testing (p<0.05), suggesting LGHAs could enhance speech perception in noisy environments.However, limitations include small sample sizes and potential biases in study design.PRMS: Demonstrated the most consistent evidence of benefit, significantly improving speech testing results, with no additional benefit from combining PRMS with other interventions.PRMS presents the most evidence-supported intervention for adults with APD, although further high-quality research is crucial for all intervention types. The establishment and implementation of standardised intervention protocols alongside rigorously validated outcome measures will enable a more evidence-based approach to managing APD in adults.